Crystalline borophene quantum dots and their derivative boron nanospheres. Issue 10 (10th May 2021) - Wang, Huiqi; An, Duo; Wang, Mei; Sun, Liwen; Li, Ying; Li, Hairu; Li, Ning; Hu, Shengliang; He, Yan-Bing
Abstract : An efficient strategy was proposed to prepare crystalline borophene quantum dots with two-photo fluorescence and their derivative boron nanospheres. Abstract : Crystalline borophene quantum dots with two-photo fluorescence and their derivative boron nanospheres with hydrazine hydrate-dependent photoluminescence properties were prepared by an efficient high-power sonication method combined with chemical exfoliation and a one-step chemical coupling strategy, respectively. This work would extend the practical lighting applications of B-rich nanomaterials.